EFISIENSI ANGGARAN DALAM MANAJEMEN KEUANGAN SEKOLAH DI DAERAH TERPENCIL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Budget constraints are one of the main challenges faced by remote schools in efforts to improve the quality of education. These limitations hinder the provision of facilities, learning media, and teacher competency development required for the implementation of the Merdeka Curriculum. Although the School Operational Assistance (BOS) fund serves as the primary source of funding, few studies have thoroughly examined budget efficiency strategies implemented by remote schools with various limitations. A research gap exists in the lack of a financial management model that integrates efficiency, accountability, and community participation simultaneously in small schools. This study aims to analyze budget efficiency–based financial management strategies applied in schools and to assess how transparency and community involvement support the improvement of education quality. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using Miles & Huberman’s interactive model: data reduction, data display, and verification. The results indicate that budget efficiency is achieved through planning based on actual needs, targeted use of funds for learning priorities, and optimization of local resources. Routine financial transparency strengthens accountability and enhances community trust. Collaboration with local residents and Corporate Social Responsibility (CSR) programs helps reduce operational costs and expand support for educational programs. This study contributes to the development of a school financial management model based on efficiency, accountability, and participation. The findings can serve as a reference for schools with similar economic and geographical conditions to establish an effective and sustainable financial management system to improve education quality.